in APLIKASI BOX BEHNKEN DESIGN UNTUK OPTIMASI PARAMETER PROSES PADA EKSPERIMEN PEMANFAATAN LIMBAH KULIT PISANG RAJA SEBAGAI ADSORBEN METHYL ORANGE - mukhlisah, lutfiyatul (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2024)
Methyl orange is a textile dye that is harmful to the environment so it needs to be treated. One of the treatments that can be used is the adsorption technique. Adsorption is carried out using an adsorbent, one of which is by utilizing banana peel waste which is used as activated carbon by adding 1 M HCl as an activator. This study aims to determine the optimum conditions for the adsorption capacity of methyl orange on adsorbents from activated banana peel valleys. The optimum conditions carried out in this study were carbonization temperature (400 - 4500C), drying time (2 - 5 hours) and contact time (80 - 120 minutes). These parameters are designed based on the optimization of the response surface methodology (RSM) which is then randomized using the Box Behnken Design method. The method used in this study is the adsorption method using an adsorbent with 6 ppm methyl orange adsorbate as much as 25 mL then analyzed using a UV-Vis spectrophotometer. The results of the study showed that the optimum condition was an adsorbent mass of 1.5 grams with a contact time of 100 minutes using the adsorbent at a carbonization temperature of 5000C and a drying time of 2 hours with an adsorption power percentage of 93.13%.